2014
DOI: 10.1111/irv.12242
|View full text |Cite
|
Sign up to set email alerts
|

Lower number of plasmacytoid dendritic cells in peripheral blood of children with bronchiolitis following respiratory syncytial virus infection

Abstract: ObjectivesDendritic cells (DCs) are key mediators of allergic airway inflammation. Thus, it is important to understand the relationship between respiratory syncytial virus (RSV) infection and DCs, especially in children with RSV bronchiolitis.MethodsWe collected peripheral blood from 71 children with RSV bronchiolitis at the time of admission and 28 children who were followed up 3 months following admission. Flow cytometry was performed to detect dendritic cell immunophenotypes.ResultsPatients with RSV bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…We think this case report is important in that DCs could have a central role in the immune mechanism for RSV clearance. Weng et al reported that a low level of pDCs in peripheral blood indicates the development of RSV lower respiratory infections, 12 which also supports our hypothesis. Effects on DCs by MMF have not been thoroughly investigated so far.…”
Section: Discussionsupporting
confidence: 91%
“…We think this case report is important in that DCs could have a central role in the immune mechanism for RSV clearance. Weng et al reported that a low level of pDCs in peripheral blood indicates the development of RSV lower respiratory infections, 12 which also supports our hypothesis. Effects on DCs by MMF have not been thoroughly investigated so far.…”
Section: Discussionsupporting
confidence: 91%
“…It is universally held that cell apoptosis results from cascade events involving a series of highly regulated cysteine proteases (caspases) (21). Caspase-3 has been proved to function downstream of the cascade reactions, where it causes cellular death by degrading corresponding substrates in cells (22).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated circulating DCs as blood is an ethical, practical, and easily accessible sample material in a cohort study of this size. Another PASTURE subproject has assessed circulating Tregs and several other studies have investigated circulating DCs . Cryopreserved cells were used in our research because of logistical reasons.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge regarding human lung DCs is not as complete. Allergic diseases have been shown to be associated with the number of circulating DCs . Increased levels of DC‐related co‐stimulatory molecules have been found in asthma, like CD86 in serum and on the surface of B cells .…”
mentioning
confidence: 99%